The impact of technology on elite sports performance - Giblin, G.; Tor, E.; Parrington, L. (Sensoria - A journal of mind, brain and culture, 2016)
The use of technological applications is now widespread across many major sports science disciplines and the adoption of these tools to gain a 'competitive advantage' is an increasingly important feature of elite sports. These innovations have shaped the way data is collected and processed, how information is relayed between coaches and staff or to athletes, and has had a big impact on the way in which athletes are monitored in the daily training and competition environments. This review highlights and provides examples of some of the latest technologies for data collection and processing, feedback methods and training tools. We finish by discussing some considerations for sports scientists and coaches before implementing new technologies.